2005
DOI: 10.1073/pnas.0503558102
|View full text |Cite
|
Sign up to set email alerts
|

The TatA component of the twin-arginine protein transport system forms channel complexes of variable diameter

Abstract: The Tat system mediates Sec-independent transport of folded precursor proteins across the bacterial plasma membrane or the chloroplast thylakoid membrane. Tat transport involves distinct high-molecular-weight TatA and TatBC complexes. Here we report the 3D architecture of the TatA complex from Escherichia coli obtained by single-particle electron microscopy and random conical tilt reconstruction. TatA forms ring-shaped structures of variable diameter in which the internal channels are large enough to accommoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
274
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(288 citation statements)
references
References 31 publications
13
274
1
Order By: Relevance
“…Studies in E. coli have demonstrated that TatA can exist in complexes with TatB and TatBC and as a separate TatA homooligomer (25)(26)(27)(28). In addition, the TatA protein itself may form the actual pore for protein secretion (29). Based on this information, the simplest explanation is that the unprocessed form of TatA is unable to interact with itself or one or more of the Tat proteins, possibly because of an unfavorable conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in E. coli have demonstrated that TatA can exist in complexes with TatB and TatBC and as a separate TatA homooligomer (25)(26)(27)(28). In addition, the TatA protein itself may form the actual pore for protein secretion (29). Based on this information, the simplest explanation is that the unprocessed form of TatA is unable to interact with itself or one or more of the Tat proteins, possibly because of an unfavorable conformation.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus motif is always located at the junction between the n and h regions (2). Precursors bearing Tat signal peptides are transported by a membrane embedded export apparatus comprising a signal peptide recognition complex (4) and a protein-conducting channel (5). The physiological role of the Tat system is to transport fully folded proteins (1,6,7), and pathogenic bacteria deficient in Tat transport demonstrate reduced virulence, which has led to consideration of this system as a target for novel antiinfectives (8).…”
mentioning
confidence: 99%
“…Additional evidence suggests that the Tat channel faces considerably greater mechanistic challenges than does the Sec channel (Gohlke et al, 2005). Studies in E. coli demonstrated that the Tat system consists, at least, of four integral membrane proteins: TatA, TatB, TatC, and TatE (Sargent et al, 1999).…”
Section: Resultsmentioning
confidence: 99%